2021
DOI: 10.1080/02109395.2021.1950421
|View full text |Cite
|
Sign up to set email alerts
|

Study on regular habits during confinement periods and their influence on anxiety (Estudio sobre los hábitos regulares en periodos de confinamiento y su influencia en la ansiedad)

Abstract: The pandemic caused by Covid-19 has forced governments to implement restrictions on mobility and social interaction and, in some cases, even confine populations to their homes, affecting their daily habits. The sample of the present study comprised 3,500 female and 1,186 male participants, whose average age was 37.9 (M = 37.90, SD = 12.46 years). A State-Trait Anxiety Questionnaire and questions specifically designed for this study were applied in order to assess participants' daily habits regarding exercise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The former lack income, and the latter are directly affected by the economic consequences of the pandemic. It should be noted that the pandemic has acted as a trigger for anxiety mainly in the young population [27,42]. On the other hand, people who are obliged to travel to work have a stressful job because they are exposed to a possible infection, and similarly, evidence shows that those who work online are also affected by anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former lack income, and the latter are directly affected by the economic consequences of the pandemic. It should be noted that the pandemic has acted as a trigger for anxiety mainly in the young population [27,42]. On the other hand, people who are obliged to travel to work have a stressful job because they are exposed to a possible infection, and similarly, evidence shows that those who work online are also affected by anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in addition to the above, social distancing is a necessary health measure to reduce the spread of COVID-19 [25]. The scientific literature has shown that this norm has become an important anxiogenic factor [26,27]. Knowing the psychological and social consequences of the confinement process is of great interest, as the possible benefits of compulsory mass quarantine entail great costs at the psychological level [28][29][30] as well as exacerbating economic and labour crises in the population that negatively affect mental health [31].…”
Section: Introductionmentioning
confidence: 99%
“…18 Other factors also contribute to anxiety, such as lifestyle in urban areas, 46 and the confinement that is presented as another significant factor. 47 The long period of quarantine that the Peruvian population went through may have increased the possibility of acquiring mental and psychological problems, 43 , 48 like anxiety (16%). 49 Other research indicated that anxiety symptoms increased by 28% in the general population.…”
Section: Discussionmentioning
confidence: 99%